2010
DOI: 10.1038/jhg.2010.127
|View full text |Cite
|
Sign up to set email alerts
|

Methylenetetrahydrofolate reductase gene polymorphisms and cerebral palsy in Chinese infants

Abstract: Genetic polymorphisms of methylenetetrahydrofolate reductase (MTHFR) have been suggested as being associated with cerebral palsy (CP) but the evidence is uncertain. The purpose of this study was to investigate whether MTHFR gene polymorphisms contribute to the development of CP in Chinese infants. For this study, 169 health controls and 159 infants with CP including 43 cases also suffering from mental retardation (MR) were recruited. Genomic DNA was prepared from venous blood and all five single nucleotide pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 31 publications
(42 reference statements)
0
7
0
1
Order By: Relevance
“…Meanwhile, CP that was accompanied by mental retardation has the frequencies of 34.9% for CC, 48.8% for CT and 16.3% for TT. 7 Compared to other studies, it appears that the genotype frequency of the MTHFR C677T gene polymorphism in patients with cerebral palsy in Bandung was smaller compared to these studies in China and Australia. 7,13 However, compared to the studies in Israel, the frequency of the MTHFR C677T gene polymorphism in this study is greater.…”
Section: Discussionmentioning
confidence: 41%
See 1 more Smart Citation
“…Meanwhile, CP that was accompanied by mental retardation has the frequencies of 34.9% for CC, 48.8% for CT and 16.3% for TT. 7 Compared to other studies, it appears that the genotype frequency of the MTHFR C677T gene polymorphism in patients with cerebral palsy in Bandung was smaller compared to these studies in China and Australia. 7,13 However, compared to the studies in Israel, the frequency of the MTHFR C677T gene polymorphism in this study is greater.…”
Section: Discussionmentioning
confidence: 41%
“…A study conducted in China reported that there is a significant relationship between MTHFR C677T gene polymorphism and CP accompanied by severe mental retardation. 7 Human MTHFR is encoded by the MTHFR gene. This enzyme plays an important role in the metabolism of folate and homocysteine.…”
Section: Introductionmentioning
confidence: 99%
“…Cerebral palsy (CP) is a group of non-progressive motor impairment syndromes caused by lesions during early brain development that often include cognitive deficits and musculoskeletal dysfunction [1,2]. The prevalence of CP – around 2 to 3 cases per 1,000 live births – has been stable over the past 30 years [3].…”
Section: Introductionmentioning
confidence: 99%
“…Over 20 studies of CP have evaluated single nucleotide polymorphisms (SNPs) in genes that regulate the inflammatory and coagulation cascades, and polymorphisms in over 15 genes have been associated with CP (212). However, genetic association studies of CP have been hampered by multiple comparisons, small sample size and population heterogeneity, thus leading to inconsistent findings (3, 1214). …”
Section: Introductionmentioning
confidence: 99%